A multicentre, randomized controlled trial of telehealth for the management of COPD. (November 2018) - Soriano, Joan B.; García-Río, Francisco; Vázquez-Espinosa, Emma; Conforto, Jose Ignacio; Hernando-Sanz, Ascensión; López-Yepes, Luis; Galera-Martínez, Raúl; Peces-Barba, Germán; Gotera-Rivera, Carolina María; Pérez-Warnisher, M. Teresa; Segrelles-Calvo, Gonzalo; Zamarro, Celia; et al.
Abstract: Background: Evidence is needed to determine the role of telehealth (TH) in COPD management. Methods: PROMETE II was a multicentre, randomized, 12-month trial. Severe COPD patients in stable condition were randomized to a specific monitoring protocol with TH or routine clinical practice (RCP). The primary objective was to reduce the number of COPD exacerbations leading to ER visits/hospital admissions between groups. Results: Overall, 237 COPD patients were screened, and 229 (96.6%) were randomized to TH (n = 115) or RCP (n = 114), with age of 71 ± 8 years and 80% were men. Overall, 169 completed the full follow-up period. There were no statistical differences at one year between groups in the proportion of participants who had a COPD exacerbation (60% in TH vs. 53.5% in RCP; p = 0.321). There was, however, a marked but non-significant trend towards a shorter duration of hospitalization and days in ICU in the TH group (18.9 ± 16.0 and 6.0 ± 4.6 days) compared to the RCP group (22.4 ± 19.5 and 13.3 ± 11.1 days). The number of all-cause deaths was comparable between groups (12 in TH vs. 13 in RCP) as was total resource utilization cost (7912€ in TH vs. 8918€ in RCP). Telehealth was evaluated highly positively by patients and doctors. Conclusions: Remote patient management did not reduce COPD-related ER visits or hospital admissions compared to RCP within 12 months.